Characterization of Chronic Sinonasal Disease Symptoms in an Urban Homeless Population. Issue 4 (July 2020) - Itamura, Kyohei; Hur, Kevin; Ference, Elisabeth; Wrobel, Bozena; Chambers, Tamara N.
Background: The urban homeless population has increased exposure to risk factors associated with chronic rhinosinusitis (CRS). However, a gap in knowledge of the prevalence of sinonasal symptoms in these demographic limits complete understanding of CRS epidemiology. There is a need to elucidate sinonasal disease burden in this vulnerable patient population to bring awareness to any existing disparities. Objective: To assess the prevalence, severity, and associated factors of CRS clinical symptoms and health-care barriers in an urban homeless population. Methods: Homeless adults completed a sociodemographic questionnaire and the 22-item Sinonasal Outcome Test (SNOT-22) and EuroQol-5 Dimension-3 Level-Visual Analog Scale surveys. Responses were categorized by potential CRS symptoms defined as reporting at least 2 CRS cardinal symptoms. Risk factors associated with potential CRS symptoms were analyzed with multivariate regression models. Results: Fifty-six (16%) out of 341 total subjects reported potential CRS symptoms. Those with potential CRS symptoms had a higher median SNOT-22 score (53 vs 22, P < .001) than those without. Logistic regression models identified history of smoking (odds ratio [OR], 6.54; 95% confidence interval [CI], 2.04–21.04) and duration of homelessness over 3 months (OR, 3.46; CI, 1.51–7.94) as factors associated with potential CRS symptoms. Duration of homelessness over 3 months was associated with higher SNOT-22 scores (standardized beta coefficient [β], 0.48; CI, 0.39–0.57). Among those reporting 2 or more CRS cardinal symptoms, 18% had ever been seen by any physician for their symptoms. Conclusions: Our study estimates a high prevalence of potential CRS symptoms in the urban homeless population. Longer duration of homelessness was associated with potential CRS symptoms and poor CRS-specific quality of life scores. Disparities in access to care emphasize the need for increased preventive efforts designed for this unique patient group.